Association between Hemodialysis Adequacy, Family Support, and Quality of Life in Chronic Renal Failure Patients - Winata, Leo Chandra Wisnu Pandu; Putranto, Wachid; Fanani, Mohammad (Indonesian Journal of Medicine, 2017)
Background: ÃÂ Hemodialysis is one of renal replacement therapy for patients with chronic renal failure (CRF). The quality of hemodialysis is largely determined by the recommended dose of hemodialysis. Biological and psychological changes are often faced by patients undergoing hemodialysis, which can affect their quality of life. Family support is an important factor that serves as a support system for the patients to face the health problems. This study aimed to determine the association between hemodialysis adequacy, family support, and quality of life in chronic renal failure patients.Subjects and Method: This was an analitic observational study with cross sectional design. ÃÂ It was conducted at Kasih Ibu Hospital, ÃÂ Surakarta, Central Java. A total sample ofÃÂ  102 patients with chronic renal failure who underwent hemodialysis were selected for this study using random sampling. The dependent variable was quality of life. The independent variables were hemodialysis adequacy and family support. The quality of life was assessed using the WHOQoL questionnaire. The hemodialysis adequacy ÃÂ was measured by Ureum Reduction Rate (URR) formula.ÃÂ  Family support was measured by family support questionnaire. The data were analyzed using Chi Square test, Mann Whitney test, and logistic regressionResults: Patients with chronic renal failure had better quality of life if they underwent adequate hemodialysis (OR= 5.34 95% CI= 2.20 to 12.98 p= 0.001) and received strong family support (OR= 7.74; 95% CI= 3.13 to 19.13ÃÂ  p= 0.001).Conclusion: Quality of life of the patients with chronic renal failure is determined by hemodialysis adequacy and family support.Keywords: chronic renal failure, hemodialysis, adequacy, family support, quality of lifeCorespondence: Leo Chandra Wisnu Pandu Winata. Masters Programs in Family Medicine, Sebelas Maret University, Jl. Ir Sutami 36A, Surakarta. Email: leochandrawisnupw@gmail.comIndonesian Journal of Medicine (2017), 2(1): 63-72https://doi.org/10.26911/theijmed.2017.02.01.07